Dental caries risk factors in West Jakarta Primary students: A cross-sectional study - Theresia, Tiarma Talenta; Lestari, Sri; Kristanto, Cindy Vania; Winson, Angela; Astoeti, Tri Erri (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: The majority of children in Indonesia, particularly in Jakarta, continue to experience numerous dental and oral health issues, with dental caries being especially prevalent. Caries is a multifactorial disease that, in children, can be caused by personal habits or external influences. Purpose: This study aimed to determine the relationship between caries risk factors and the occurrence of caries in primary school children in West Jakarta, Indonesia. Methods: The study was conducted in three public primary schools in West Jakarta in November 2023. Oral examinations and questionnaires were completed by all students from fourth to sixth grade, with a total sample size of 421 students. In this study, caries was the dependent variable, and the independent variables included sociodemographic factors, oral health behaviors, smoking habits, and dietary habits. Data analysis involved bivariate analysis and the application of a multivariate prediction model using logistic regression. Results: The variables significantly associated with dental caries were never visiting the dentist (p < 0.05), brushing teeth never or only several times a week (p < 0.05), never consuming fruits (p < 0.05), and consuming biscuits several times a day (p < 0.05). However, other variables—such as parental education, use of oral cleaning tools and fluoride toothpaste, smoking habits, and consumption of certain sweet foods and beverages—did not show a significant association. Conclusion: The most substantial factors contributing to dental caries were infrequent toothbrushing and frequent consumption of biscuits. Interestingly, children who never visited the dentist had lower incidences of caries.